The Carnegie Supernova Project I: optical spectroscopy of stripped-envelope supernovae - Stritzinger, M. D. (2023)
We present 170 optical spectra of 35 low-redshift stripped-envelope core-collapse supernovae observed by the Carnegie Supernova Project-I between 2004 and 2009. The data extend from as early as - 19 days (d) prior to the epoch of B-band maximum to +322 d, with the vast majority obtained during the so-called photospheric phase covering the weeks around peak luminosity. In addition to histogram plots characterizing the redshift distribution, number of spectra per object, and the phase distribution of the sample, spectroscopic classification is also provided following standard criteria. The CSP-I spectra are electronically available and a detailed analysis of the data set is presented in a companion paper being the fifth and final paper of the series.